Double whammy! The dysphemistic euphemism implied in unVables such as unmentionables, unprintables, undesirables - Chris Smith (Lexis: Journal in English Lexicology)
The starting point for this paper is the realization that the classic euphemism unmentionables rests upon three word formation processes, which have each been proven to be individually compatible with euphemistic effect. Consider the Oxford English Dictionary (OED) entry for the plural noun unmentionable (1823): “b) n. pl. Trousers. (Cf. inexpressible n. 2) Also, underpants, and (chiefly joc.) underwear, esp. women’s. (1823); - c) n. A person or thing not to be mentioned (by name). Chiefly pl. (1928)”. The existence of a whole class of euphemistic unVables built on the same model, such as unprintables (OED, first occurrence 1860 in the sense of trousers), untouchables (lexicalized 1909 in the sense of “Indian underclass”), unspeakables (lexicalized, 1823 in the sense of “ineffable being”), has motivated research into the role of A>N conversion, metonymy and the unVable double affixation on the final connotations of the expression. The purpose of the paper is to present a case study of unVables: by producing a list of attested unVables, I investigate the correlation between lexical complexity and lexical creativity and euphemism. The data collected shows that, despite no longer being lexicalized, the unVables metonyms continue to be used in a context of lexical expressiveness. The paper takes the view that the position of unVables on the positive end of the X-phemism pole has shifted over time to metalinguistically produce a dysphemistic effect. This shift can partly be justified by changing perceptions of taboo areas, but also, crucially, to the inherent deontic shift of the unVable derivative. Ultimately, the use of unVables today tends to lay focus on the self-censure at the heart of the expression, thus creating a contrast between the minimizing features of euphemism and the maximizing features of a focusing process.